READING HABITS AND THE STUDENTS’ READING COMPETENCY IN THE JUNIOR SECONDARY SCHOOL IN SINGARAJA - ., Made Lady Agustina; ., Prof. Dr. Dewa Komang Tantra, M.Sc.; ., Gede Mahendrayana, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk mengetahui kebiasaan membaca dan kompetensi membaca pada deskriptif teks serta hubungan antara dua variable. Penelitian ini dirancang dalam metode kuantitatif korelasil. Populasi penelitian siswa kelas VII di SMPN 5 Singaraja yang berjumlah 352 siswa sedangkan sample penelitian ini yaitu siswa kelas VII F dan VII K yang berjumlah 64 siswa. Sample penelitian ini menggunakan purposive random sampling. Penelitian ini menggunakan dua instrument yaitu angket kebiasaan membaca dan tes kompetensi membaca. Angket kebiasaan membaca digunakan untuk memperoleh data kebiasaan membaca siswa dan tes kompetensi membaca digunakan untuk memperoleh data kompetensi siswa. Data yang diperoleh dianalisis dengan menggunakan langkah- langkah deskriptif dan koefisien korelasi Pearson’s Product Moment. Hasil dari penelitian ini adalah ada hubungan yang positif antara kebiasaan membaca siswa dan komptensi membaca. Kata Kunci : Kebiasaan Membaca, Kompetensi Membaca, Koefisien Korelasi The current research objectives were focused on the students’ reading habits and reading competency on descriptive profiles as well as the relationships between the two variables. This research was designed in a correlation quantitative methodology. The population was seventh grade students of SMPN 5 Singaraja consist of 352 while the sample was VII F and VII K class which consisted of 64 students. The samples were selected by purposive random sampling. The two instruments consisted of reading habits questionnaire and reading competency test. Questionnaire was used to obtain the data of students’ reading habits and reading test to obtain the data of reading competency. The obtained data were analyzed using descriptive measures and Pearson’s Product Moment Correlation Coefficient. The research findings showed that there is a significant positive correlation between students’ reading habits and their reading competency. keyword : Reading Habits, Reading Competency, Correlation Coefficient.